1999
DOI: 10.1108/09576069910247573
|View full text |Cite
|
Sign up to set email alerts
|

Why British companies don’t do effective benchmarking

Abstract: The authors are grateful to the Control, Design and Production Group of the Engineering and Physical Sciences Research Council (EPSRC) for the award of a research grant to undertake the research described in this paper. They are also grateful to the companies in which field studies were undertaken.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 8 publications
1
16
0
Order By: Relevance
“…Strategic Change Management. The fact that the adoption of a best practice is not managed strategically is another highly consistent theme across the reviewed research studies (Bateman and Rich 2003; Bessant et al 1999, 2003; Davies and Kochhar 1999; Dixon et al . 1994; Drew 1994; Guimaraes 1999; Longbottom 2000; Petroni 2002; Taylor and Wright 2003).…”
mentioning
confidence: 77%
See 2 more Smart Citations
“…Strategic Change Management. The fact that the adoption of a best practice is not managed strategically is another highly consistent theme across the reviewed research studies (Bateman and Rich 2003; Bessant et al 1999, 2003; Davies and Kochhar 1999; Dixon et al . 1994; Drew 1994; Guimaraes 1999; Longbottom 2000; Petroni 2002; Taylor and Wright 2003).…”
mentioning
confidence: 77%
“…54% of supply chain partnering fails (Boddy et al . 1988). Although UK companies conduct benchmarking activities and identify best practices, they do not go through any implementation efforts, often because the performance gap is so large that it seems impossible to bridge (Davies and Kochhar 1999, 2000). …”
Section: Evidence Of a Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, benchmarking can be described as a method of converting process data to relevant process information from which process knowledge and understanding can be developed. Indeed, Davies and Kochhar (1999) proposed that in benchmarking there was often a preoccupation with metrics, to the exclusion of the identification of best practices. Whole supply chain or whole farm benchmarking will provide information on supply chain/organisational structure, its strengths and weaknesses and the areas of business risk.…”
Section: Introductionmentioning
confidence: 99%
“…These reasons can prevent companies and organizations from participating in an accurate and reliable benchmarking process. Davies & Kochar (1999); Adebanjo et al (2010) suggested that in order to eliminate these barriers to adoption and growth of benchmarking, education and awareness of top management, training and benchmarking skills development are keys to promote benchmarking across all areas of an organization. However, benchmarking needs top management support and employee participation, education and training to succeed (Lee, 2006).…”
Section: Barriers Of Benchmarkingmentioning
confidence: 99%